Ethical Leadership and Corporate Social Responsibility: A Comprehensive Review - Zhu Kongjue; Zhao Yuxiang, (International Journal of Advances in Business and Management Research (IJABMR), 2024)
The topics of ethical leadership and corporate social responsibility (CSR) have become more prominent in the business domain. The topic related to moral authorities, the connection between corporate social responsibility (CSR), and commercial achievement has received considerable interest from both academic and organizational spheres in recent years. Indeed, a multitude of research articles and specialized journal issues have focused specifically on these three areas. This research provides a thorough evaluation of the concepts of moral leadership as well as corporate social responsibility (CSR) and their impact on company performance. This comprehensive review article analyses the fundamental principles, concepts, and empirical evidence pertaining to ethical leadership and corporate social responsibility (CSR). This research examines the correlation between ethical leadership and corporate social responsibility (CSR) policies, investigating their impact on business performance, employee involvement, and society's welfare. The article also analyses the challenges and possible benefits of integrating ethical leadership and corporate social responsibility (CSR) into business strategies. This study aims to provide a thorough understanding of the significance of ethics and social responsibility in contemporary corporate management by integrating research from other disciplines.